Analisis Kompetensi Cooking Skills Terhadap Kinerja Karyawan di RM. Daeng Bakar Kota Majene - Rahmita Rahmita; Amiruddin Tawe; Rezky Amalia Hamka (Jurnal Visi Manajemen, 2024)
This study aims to determine how the Competence of Cooking skills on Employee Performance at RM. Daeng Bakar Majene City. The method used is Descriptive Qualitative.The sample in this study were employees at RM. Daeng Bakar Majene City. The data collection technique is Interview, Observation, and Documentation. The data analysis technique uses Miles and Huberman's theory, namely reducing data, presenting data, and concluding data. The results showed that there was a link between Competent Cooking Skills and Employee Performance at RM. Daeng Bakar Majene City, that the competence of cooking skills will maintain the taste of cooking, increase profits and also employee performance.